Defective Mitochondrial Fatty Acid Oxidation and Lipotoxicity in Kidney Diseases - Jang, Hee-Seong; Noh, Mi Ra; Kim, Jinu; Padanilam, Babu J. (Frontiers in Medicine, 2020)
The kidney is a highly metabolic organ and uses high levels of ATP to maintain electrolyte and acid-base homeostasis and reabsorb nutrients. Energy depletion is a critical factor in development and progression of various kidney diseases including acute kidney injury (AKI), chronic kidney disease (CKD), and diabetic and glomerular nephropathy. Mitochondrial fatty acid β-oxidation (FAO) serves as the preferred source of ATP in the kidney and its dysfunction results in ATP depletion and lipotoxicity to elicit tubular injury and inflammation and subsequent fibrosis progression. This review explores the current state of knowledge on the role of mitochondrial FAO dysfunction in the pathophysiology of kidney diseases including AKI and CKD and prospective views on developing therapeutic interventions based on mitochondrial energy metabolism.